The analysis of the agricultural holdings structure in the communes Bisoca, Pietroasele and Gherăseni, Buzau County - Raluca Necula; Diana Necula (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 4th Edition of the International Symposium, November 2013, Bucharest, 2013)
This paper represents a first part of a larger study on three villages in Buzau County using a questionnaire implemented in three different geographical areas villages. There are showed some descriptive statistics based on data from the questionnaire. These statistics help us to better illustrate the reality of the analyzed villages. Are shown agricultural holdings structures by the owned group area and after the exploited area, aiming to describe the exploatation area level, the agricultural machinery provision and the production disposed for sale. All these manage to outline a picture of agricultural holdings in Buzau county, image needed to find solutions to the county agriculture development.
Keywords: 330; agricultural holdings; surface owned; exploited surface; agricultural machinery; production